1982
DOI: 10.1073/pnas.79.13.4193
|View full text |Cite
|
Sign up to set email alerts
|

Platelets of pseudohypoparathyroid patients: Evidence that distinct receptor-cyclase coupling proteins mediate stimulation and inhibition of adenylate cyclase

Abstract: We studied platelets of patients with the genetic disorder pseudohypoparathyroidism (PHP) to test whether the nucleotide-binding proteins mediating stimulation of adenylate cyclase (termed NS) are identical to those mediating inhibition of cyclase (termed Ni). Functional responses to hormones that work through stimulation of adenylate cyclase are blunted in PHP patients. The erythrocytes of many of these patients (PHP-Ia) have previously been shown to have decreased Ns activity whereas those of other PHP patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

1983
1983
1998
1998

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 25 publications
2
6
1
Order By: Relevance
“…This component is the G unit, and it is apparent from our current results that a deficiency of G units can impair the ability of an intact cell to accumulate cAMP in response to hormone stimulation and can impair adenylate cyclase activation of membranes by agents acting via the G unit. A similar conclusion can be drawn from data recently reported by Motulsky et al (32). Although Bourne et al (23) were unable to see a significant difference in cAMP response to PGE1 in intact fibroblasts derived from control subjects vs. patients with PHP, the same investigators (32) found deficient G-unit activity in platelet membranes as well as reduced cAMP response to prostacyclin in intact platelets from patients with PHP.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…This component is the G unit, and it is apparent from our current results that a deficiency of G units can impair the ability of an intact cell to accumulate cAMP in response to hormone stimulation and can impair adenylate cyclase activation of membranes by agents acting via the G unit. A similar conclusion can be drawn from data recently reported by Motulsky et al (32). Although Bourne et al (23) were unable to see a significant difference in cAMP response to PGE1 in intact fibroblasts derived from control subjects vs. patients with PHP, the same investigators (32) found deficient G-unit activity in platelet membranes as well as reduced cAMP response to prostacyclin in intact platelets from patients with PHP.…”
Section: Methodssupporting
confidence: 74%
“…A similar conclusion can be drawn from data recently reported by Motulsky et al (32). Although Bourne et al (23) were unable to see a significant difference in cAMP response to PGE1 in intact fibroblasts derived from control subjects vs. patients with PHP, the same investigators (32) found deficient G-unit activity in platelet membranes as well as reduced cAMP response to prostacyclin in intact platelets from patients with PHP.…”
Section: Methodssupporting
confidence: 74%
“…Other reasons for their different conclusion are that their samples were stored for long periods and thcir basal FFA levels were well above the upper limit of normal values. G,-mediated events in platelets have been reported to be normal in PHPT (21). The inhibition of adipocyte adenylate cyclase via the adenosine A l receptor was normal in our patients, which is in contrast with what is usually found in obesity (4.…”
Section: Discussioncontrasting
confidence: 83%
“…Activation and inhibition of adenylate cyclase are differentially sensitive to Mn2+ (10), GTP (10)(11)(12), and chemical modification by N-ethylmaleimide (6,13). Platelets from pseudohypoparathyroid patients are functionally deficient in Ns but express both epinephrine-mediated inhibition of adenylate cyclase and GTP-sensitive high-affinity binding of agonists to a2-adrenergic receptors, suggesting that N1 is fully functional in these cells (14). Furthermore, cyc-S49 lymphoma cells lack functional Ns but express active N, (15).…”
Section: Activation Of Muscarinic Cholinergic Receptors Results In At-mentioning
confidence: 99%